Selection and validation of reference genes for qRT‐PCR analysis during fruit ripening of red pitaya (Hylocereus polyrhizus) - Qianming Zheng; Xiaoke Wang; Yong Qi; Yuhua Ma (FEBS Open Bio)
Red pitaya (Hylocereus polyrhizus) is widely cultivated in southern and southwestern China. To provide a basis for studying the molecular mechanisms of the ripening of this fruit, we carried out RNA sequencing (RNA‐seq) analysis to identify differentially and stably expressed unigenes. The latter may serve as a resource of potential reference genes for normalization of target gene expression determined using quantitative real‐time PCR (qRT‐PCR). We selected 11 candidate reference genes from our RNA‐seq analysis of red pitaya fruit ripening (ACT7, EF‐1α, IF‐4α, PTBP, PP2A, EF2, Hsp70, GAPDH, DNAJ, TUB and CYP), as well as β‐ACT, which has been used as a reference gene for pitayas in previous studies. We then comprehensively evaluated their expression stability during fruit ripening using four statistical methods (GeNorm, NormFinder, BestKeeper and DeltaCt) and merged the four outputs using the online tool RefFinder for the final ranking. We report that PTBP and DNAJ showed the most stable expression patterns, whereas CYP and ACT7 showed the least stable expression patterns. The relative gene expression of red pitaya sucrose synthase and 4, 5‐dihydroxyphenylalanine‐extradiol‐dioxygenase as determined by quantitative real‐time PCR and normalized to PTBP and DNAJ was consistent with the RNA‐seq results, suggesting that PTBP and DNAJ are suitable reference genes for studies of red pitaya fruit ripening.